The biology and fishery of mud crab, genus scylla in east Malaysia - Mohd. Ikhwanuddin, @ Polity Bin Abdullah. (Universiti Malaysia Sarawak, (UNIMAS), 2001)
The study was conducted to determine the biological information and fishery statistics of mud crab, genus scylla in selected mangrove ecosystems within East Malaysia. The main study site was the Sematan mangrove forest with three other minor study sites; Brunei Bay, Marudu Bay and the Island of Banggi.